Back to basics: tackling security threats in an increasingly complex world. Issue 7 (July 2019) - Fielding, Jon
Abstract : Something strange is happening to the world of IT. As technological innovation drives businesses to become more productive, innovative and agile, it's simultaneously driving those tasked with protecting these new networks and systems to breaking point. Complexity might be hidden from the end user, but it's making the job of the IT security function more challenging by the day. As technological innovation drives businesses to become more productive, innovative and agile, it's simultaneously driving those tasked with protecting these new networks and systems to breaking point. Complexity might be hidden from the end user, but it's making the job of the IT security function more challenging by the day. This can sometimes make it difficult for security practitioners to filter out the noise and remember what's really important. Organisations need to focus on the end user and adopt basic best practices to ensure their security is built on a solid foundation, argues Jon Fielding of Apricorn.